GreenLight laser for prostates over 100 ml: what is the evidence?. Issue 1 (January 2016) - Stone, Benjamin V.; Chughtai, Bilal; Kaplan, Steven A.; Te, Alexis E.; Lee, Richard K.
Abstract : Purpose of review: GreenLight photoselective vaporization of the prostate (PVP) has emerged as a minimally invasive, well tolerated, efficacious alternative to transurethral resection of the prostate (TURP) or simple prostatectomy for the treatment of benign prostatic hyperplasia. However, some authors have expressed concern with the use of PVP in large prostates. In this review, we present the most relevant recent literature regarding PVP for treatment of benign prostatic hyperplasia in prostates over 100 ml. Recent findings: Recent studies have found that the subjective and objective outcomes of GreenLight PVP, including International Prostate Symptom Score, quality of lifescore, maximum urinary flow rate, and postvoid residual are comparable in large and small prostates. Though larger glands require increased operative time, energy delivery, and fiber use, the short duration of hospitalization and catheterization does not vary with prostate size. The overall complication rates do not increase with prostate size, though some studies have reported increased conversion to electrocautery TURP hemostasis. The trend toward increased retreatment rates in some studies of PVP in large prostates may be because of inadequate energy density delivered. Summary: GreenLight photoselective PVP is a well tolerated and efficacious procedure regardless of prostate size, and should therefore be considered as a viable alternative to TURP, holmium laser enucleation of the prostate, or simple prostatectomy in large prostates.